Experimental Study on Performance of Centrifugal Pump - Baloni, Beena; Shah, Maitrik; Channiwala, Salim Abbasbhai (International Conference Fluid Power 2025: Conference Proceedings, 2025)
A centrifugal pump is designed to enhance the fluid pressure head through energy transfer. Fluid enters the impeller axially, which increases the fluid velocity and pressure by converting mechanical energy. The present work aims to conduct an experimental performance analysis of a centrifugal pump. The experimental test setup as per ISO 9906 (grade 1) is developed for better accuracy and minimum uncertainty. The experimental analysis is carried out, for the 7.5 hp end suction pump, at various speeds and valve opening positions. After conducting a repeatability test, the performance curves are obtained at various operating conditions. The performance curves identified the best efficiency region by varying valve positions in the interval of 1% in the optimum region. At BEP, the head coefficient ranges from 0.90 to 0.82, the flow coefficient from 0.16 to 0.13, and the pump efficiency from 66 % to 63 %, depending on the pump speed.